Brisk Walking Untuk Menurunkan Kadar Glukosa Darah Pada Pasien Diabetes Mellitus Tipe 2: A Literature Review - Magenda Bisma Yudha; Nur Intan Kartika Sari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: One of the non-communicable diseases (NCDs) that has received a lot of attention is Diabetes Mellitus. Diabetes management is divided into two ways. The first way is with non-drug therapy (non-pharmacological) and second with drug therapy. Drug therapy in the form of oral hypoglycemic drugs or insulin. Non-pharmacological methods with food planning and physical exercise. The type of light physical exercise recommended for patients with type II diabetes mellitus is walking and brisk walking. Objective: To determine the effect of brisk walking to reduce blood glucose levels in patients with type 2 diabetes mellitus. Methods: This review uses the literature review method. Searches were conducted in PubMed, Garuda, and Google Scholar. The search strategy used keywords with